The myrosinase-glucosinolate system to generate neoglycoproteins: A case study targeting mannose binding lectins. (June 2022) - Cutolo, Giuliano; Didak, Blanka; Tomas, Josip; Roubinet, Benoit; Lafite, Pierre; Nehmé, Reine; Schuler, Marie; Landemarre, Ludovic; Tatibouët, Arnaud
Abstract: A convenient strategy for a 'one-pot' synthesis of neoglycoproteins (NGP) was developed using the myrosinase-glucosinolate couple, a natural enzyme-substrate system. This enzymatic reaction allowed us to generate an isothiocyanate in situ which then reacted with the lysine residues of bovine serum albumin protein (BSA) to produce multivalent neoglycoproteins. Using two models, glucomoringin which is a natural glucosinolate bearing a l -rhamnose unit, and an artificial glucosinolate specifically designed for mannose type lectins, an average of up to 17.8 and 28.7 carbohydrate residues could be respectively grafted onto the BSA protein. This process is comparable to commercial approaches using BSA-ManC without the disadvantage of handling harmful chemical reagents. Lectin binding screening (GLYcoPROFILE®) showed that among all NGPs synthesized, BSA-Man 16 gave similar and in some cases better affinities in comparison with commercial BSA-Manc towards various mannose-specific lectins. Graphical abstract: Image 1 Highlights: Enzymatically induced isothiocyanate formation through a Lossen rearrangement. A natural myrosinase-glucosinolate/enzyme-substrate system used for bioconjugation. A one-pot strategy for the preparation of neoglycoproteins without isothiocyanate handling.